(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
In Ukrainian linguistics it is traditional to study the semantic groups of the vocabulary of the language. One of these groups is odorativa. The clarification of the history of the formation of a separate semantic group - obnoxious - is relevant because it allows us to broaden the general picture of the world. Our article is devoted to the description of the thematic group of tokens on the designation of smells of the ancient Russian-Ukrainian period, since a complete study of the history of the lexical composition of the Ukrainian language is impossible without an understanding of the history of the formation of individual semantic groups. The surveyed sources of the period of Kievan Rus allow to distinguish thematic groups that were recorded in the pre-Slavic period. This is a group of fragrant plants (about 20 tokens). In some contexts we observe a number of names of fragrant plants. Individually analyzed tokens may be included in different thematic groups (plants, substances). The group of aromatic substances was the most quantitative (almost 60 nomens). Mostly, in ancient texts, there were obsessive religious usage tokens. The peculiarity of the thematic group of aromatic substances is the presence of word-formation nests. Similar word-building nests contain a variety of variants. The most productive word-building nest of this period of the analyzed thematic group are derivatives with the root of the world. The non-derivative world-class token was ambiguous and performed in various ways. About a dozen derivatives are formed by the foundation. Preferably nouns and adjectives. A number of nomines were used in the monuments to designate the kind of spices. Found many-valued nouns, verbs, contextually conveying obsessive feelings.